INVESTIGATING THE BIOCHEMICAL PROFILE AND NUTRITIONAL COMPOSITION OF VERNONIA AMYGDALINA LEAVES: A STUDY ON ANTIOXIDANT PROPERTIES, PHYTOCHEMICAL COMPOSITION, ENZYME INHIBITION, AND PROTEIN ACTIVITY - Olugbenga D. Oloruntola; Fehintoluwa S. Oladebeye; Samuel A. Adeyeye; Simeon O. Ayodele; Ojurereoluwa A. Ayodele; Olufemi E. Adeniji (Acta Scientifica Malaysia)
In this comprehensive study, the biochemical profile and nutritional composition of Vernonia amygdalina leaves were examined, focusing on their antioxidant properties, phytochemical composition, enzyme inhibition, and protein activity. A meticulous extraction process using 70% ethanol yielded an ethanolic extract of Vernonia amygdalina leaves powder (VLP), which exhibited substantial Vitamin C content (12.95 mg/g) and impressive antioxidant activity, as evidenced by a 2,2-diphenyl-1-picrylhydrazyl hydrate value of 60.24% and a ferric ion reducing antioxidant power value of 49.22 mg/g. The extract also demonstrated a significant 49.01% inhibition of lipid peroxidation, highlighting its potential in mitigating oxidative stress. Phytochemical analysis revealed the presence of flavonoids, alkaloids, phenols, saponins, and tannins, further emphasizing the therapeutic potential of Vernonia amygdalina. Moreover, the study unveiled the extract’s inhibitory effects on key enzymes and proteins involved in metabolic processes, with notable rates of 29.34% for anti-glucosidase activity, 43.28% for alpha-amylase inhibition, 34.44% for albumin denaturation inhibition, and 57.04% for anti-proteinase activity. Additionally, the proximate analysis showcased the leaf’s composition, with 14.13% crude protein, 23.53% crude fiber, 0.81% crude fat, 7.10% ash content, and 41.16% nitrogen-free extracts, underscoring its potential as a valuable source of dietary protein and fiber. These findings collectively emphasize the multifaceted health-promoting properties and nutritional value of Vernonia amygdalina leaves, advocating their utilization in various dietary and therapeutic applications.